PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KEPRIBADIAN SEBAGAI VARIABEL MODERATING (STUDI DI PT. MARGAMAS INDAH DEVELOPMENT MAKASSAR) - Novin Christy Anasthasia; Mahlia Muis; Wahda - (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2019)
This research aims to determine the effect of leadership style and motivation variables on employees’ performance with personality as moderating variable at PT. Margamas Indah Development (MID) of Makasasar. This research was a descriptive quantitative study. The populations were employees at PT. MID of Makassar. The sample consisted of 30 employees working at PT. MID of Makassar. The methods of data collection were questionnaire, interview, observation, and documentation and the data were analyzed using Partial Least Square (PLS). The results of the research indicate that leadership style has a positive and significant effect o employees’ performance. Personality can moderate (weaken) the ffect of leadership style on employees’ performance, and it can also moderate (strengthen) the effect of motivation on employees’ performance. Keywords: leadership style, motivation, employees’ performance, personality.